Once in the XX century / Deimantas Narkevicius. - Narkevičius, Deimantas (Arnolfini, 2006)
This book was published on the occasion of the first one-person exhibition in the UK, Once in the XX Century, by Lithuanian artist Deimantas Narkevicius held 6 May-2 July, 2006 at the Arnolfini Gallery, Bristol